Recent Directions in War Memorial Design - Stephens, John (Common Ground Publishing Pty Ltd, 2012)
In the past two decades there has been a rise in the number of people attending war commemoration ceremonies in Australia. This rise can be seen abroad as well -- notably at Gallipoli (Turkey) and more recently at Villiers Bretonneaux (France). In tandem, there has been a resurgence of interest in the Australian cultural phenomenon of 'Anzac' as a purveyor of national values and a rise in the number of war memorials built in Australia. This passion for remembering and commemorating war is also evident in other countries across the world. The cataclysmic events of the First World War triggered an initial wave of memorial building across Australia based mostly on cemetery architecture derived from classical forms. This design trend continued after the Second World War and forms such as obelisks are still favoured by some Australian communities. Recently however, there has been a discernible shift from traditional and classically designed war memorials to abstract and highly narrative memorials -- a trend that has not been without some controversy. Set against a rising tide of commemorative activity, this paper will explore how recent war memorial designs are re-imagining the landscape of war remembrance in Australia.